Osteogenic Monocytes within the Coronary Circulation and their Association with Plaque Vulnerability in Patients with Early Atherosclerosis - Collin, Julia (Int J Cardiol, 2014)
OBJECTIVES: This study tests the hypothesis that circulating mononuclear cells expressing osteocalcin (OCN) and bone alkaline phosphatase (BAP) are associated with distinct plaque tissue components in patients with early coronary atherosclerosis. BACKGROUND: Plaque characteristics implying vulnerability develop at the earliest stage of coronary atherosclerosis. Increasing evidence indicates that cells from the myeloid lineage might serve as important mediators of destabilization. Plaque burden and its components were assessed regarding their relationship to monocytes carrying both pro-inflammatory (CD14) and osteogenic surface markers OCN and BAP. METHODS: Twenty-three patients with angiographically non-obstructive coronary artery disease underwent coronary endothelial function assessment and virtual histology-intravascular ultrasound of the left coronary artery. Plaque composition was characterized in the total segment (TS) and in the target lesion (TL) containing the highest amount of plaque burden. Blood samples were collected simultaneously from the aorta and the coronary sinus. Circulating cell counts were then identified from each sample and a gradient across the coronary circulation was determined. RESULTS: Circulating CD14+/BAP+/OCN+ monocytes correlate with the extent of necrotic core and calcification (r=0.53, p=0.010; r=0.55, p=0.006, respectively). Importantly, coronary retention of CD14+/OCN+ cells also correlate with the amount of necrotic core and calcification (r=0.61, p=0.003; r=0.61, p=0.003) respectively. CONCLUSIONS: Our study links CD14+/BAP+/OCN+ monocytes to the pathologic remodeling of the coronary circulation and therefore associates these cells with plaque destabilization in patients with early coronary atherosclerosis.